1996
DOI: 10.1620/tjem.179.227
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production of Inflammatory Cytokines in Cultured CD4+ Cells from Patients with HTLV-I-Associated Myelopathy.

Abstract: We investigated the production of inflammatory cytokines derived from cultured T cells of peripheral blood lymphocytes (PBL) in 14 patients with HTLV-I-associated myelopathy (HAM). The production of inflammatory cytokines, such as tumor necrosis factor-alpha, interferon-gamma, and granulocyte-macrophage colony stimulating factor, was significantly increased in patients with HAM, compared to HTLV-I seronegative controls. On the contrary, interleukin-4 production in cultured T cells was detected in only two pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
2
28
0
1
Order By: Relevance
“…We conclude that the high frequency of HTLV-I-specific CD4 ϩ T cells was associated with the disease HAM/TSP. This conclusion is corroborated by evidence from several sources: 1) the predominant T cell in early HAM/TSP lesions is the CD4 ϩ T cell (8); 2) HTLV-I-infected CD4 ϩ T cells spontaneously produce proinflammatory cytokines (11,12,18); 3) activated CD4…”
Section: Figure 3 Detection Of Cmv-specific Cd4mentioning
confidence: 70%
See 3 more Smart Citations
“…We conclude that the high frequency of HTLV-I-specific CD4 ϩ T cells was associated with the disease HAM/TSP. This conclusion is corroborated by evidence from several sources: 1) the predominant T cell in early HAM/TSP lesions is the CD4 ϩ T cell (8); 2) HTLV-I-infected CD4 ϩ T cells spontaneously produce proinflammatory cytokines (11,12,18); 3) activated CD4…”
Section: Figure 3 Detection Of Cmv-specific Cd4mentioning
confidence: 70%
“…In particular, the spontaneous proliferation (34 -36) and spontaneous cytokine production (12,15,18) associated with HTLV-I infection complicate assays of both T cell proliferation and cytokine detection. To overcome these problems, we recently established 6-h ELISPOT and intracellular cytokine staining assays and detected significant frequencies of Env and Tax-specific CD4 ϩ T cells in infected subjects (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular interest, HAM/TSP patients display an activated inflammatory immune response associated with a decreased suppressive capacity in Treg cells (Nishiura et al 1996). In contrast, it has been demonstrated that the immunocompromised state seen in ATLL patients may be a result of clonal expansion of a Treg precursor, suppressing anti-tumor immunity ).…”
Section: Discussionmentioning
confidence: 99%